Dimensions of Personality Pathology in Adolescents: Psychometric Properties of the DAPP-BQ-A - Tromp, Noor B.; Koot, Hans M. (Journal of personality disorders, 2008)
This study aimed to contribute to the dimensional approach to personality pathology by addressing the applicability of a personality pathology questionnaire, originally developed for adults, in adolescent samples. The psychometric properties of the Dimensional Assessment of Personality Pathology-Basic Questionnaire for Adolescents (DAPP-BQ-A) were studied in two samples including 170 adolescents referred for mental health services and 1,628 nonreferred adolescents, respectively. Factor analysis resulted in a strong replication of the original structure, retaining four factors (Emotional Dysregulation, Dissocial Behavior, Inhibitedness, and Compulsivity), which could be further organized into a two-dimensional structure with factors identifiable as Internalizing and Externalizing, suggesting a possible link between personality and psychopathology. Internal consistency and test-retest reliability proved to be satisfactory for all lower-order dimensions, with the exception of Intimacy Problems. Several of these dimensions showed considerable promise in differentiating nonreferred adolescents, referred adolescents without and referred adolescents with a personality disorder. The present findings underscore the need for a developmental perspective on personality pathology. Promising aspects of the dimensional approach to personality pathology in adolescence are discussed.